A feeding-directional cutting force model for end surface grinding of CFRP composites using rotary ultrasonic machining with elliptical ultrasonic vibration. (May 2020) - Wang, Hui; Pei, Z.J.; Cong, Weilong
Abstract: End surface grinding of carbon fiber reinforced plastic (CFRP) composites using RUM with elliptical ultrasonic vibration has been proven to be effective in improving surface quality and simultaneously decreasing cutting forces. The cutting force is considered as one of the key output variables to evaluate the machining performance of the cutting process. Investigating cutting force and its modeling development provides great help to understand the effects of input variables and material removal mechanisms of RUM end surface grinding of CFRPs with elliptical ultrasonic vibration. However, there is no investigation on modeling cutting force for this process. This investigation will, for the first time, present a mechanistic feeding-directional cutting force model for such a process. This model is developed based on the material removal mode of brittle fracture. The approaches of the modeling development start from the analysis of one single abrasive grain, including the material removal volume, the effective cutting time, the average indentation depth, and the impact grain force in one ultrasonic vibration cycle. The designed pilot experiments are performed to verify this mechanistic model. The trends of predicted cutting forces are consistent well with those of experimental results. In addition, it can be also applied for predicting the effects of input variables (including depth of cut, feedrate, tool rotation speed, ultrasonic amplitude, abrasive size, and abrasive concentration) on feeding-directional cutting forces. Graphical abstract: Image 1007 Highlights: A mechanistic model is developed for RUM end surface grinding of CFRP composites with elliptical ultrasonic vibration. The interaction between the abrasive grain and workpiece is intermittent. The tool-workpiece contacting area is analyzed. The effective cutting time in one ultrasonic cycle is calculated. The relationship between indentation depth and MRR is established.